Improving Teacher Performance in Educational Institutions at Semen Indonesia Foundation: The Mediating Role of Work Motivation between Work Discipline and Training - Febrianti, Siska; Soelistya, Djoko (Journal La Edusci, 2025)
This study aims to analyze and test the Teacher performance variables at Semen Indonesia Foundation under the auspices of PT Semen Gresik. Both direct and indirect influences between variables. The research method used in this study is quantitative. The population in this study were all Employees at Semen Indonesia Foundation under the auspices of PT Semen Gresik. Data analysis test using the SEM PLS model with the Smart PLS version 4.0 test tool. with saturated sampling of 100 respondents. From the hypotheses presented, the results of this study indicate that Work Discipline has a positive and significant effect on Teacher performance. Training has a positive and significant effect on Teacher performance. Work Discipline has a positive and significant effect on Motivation. Training has a positive and significant effect on Motivation. Motivation has a positive and significant effect on Teacher performance. Work Discipline has a positive and significant effect on Teacher performance through full Work Motivation. Training has a positive and significant effect on Teacher performance through full Work Motivation. This study provides new insights or expands existing theories and provides research implications that are explained practically and theoretically, and through the implementation of clear rules, reward and punishment systems, and extraordinary leadership, companies can improve their employees' performance. In addition, discipline and training that are evaluated periodically and based on employee needs can improve work skills and motivation. Employees should also be encouraged through performance-based rewards, career development opportunities, a positive work environment, and work flexibility that supports life balance.